Um estudo fuzzy para propor um modelo matemático como auxílio ao diagnóstico médico das faringotonsilites - Pissini, Mariana Moretto (2019)
Medical practice consists of a continuous decision-making process and Fuzzy Logic has participated in this process. In this context, this research has as main objective to carry out a study on basic concepts of Fuzzy Set Theory and an application of this study to propose a mathematical model as an aid to the medical diagnosis of patients infected with certain diseases in the upper respiratory tract. The following diseases were considered: viral pharyngotonsillitis, streptococcal pharyngotonsillitis, mononucleosis and diphtheria; and fuzzy relational equations were used to propose a medical diagnostic model relating the symptoms or signs of patients with these four diseases.